Role Expectation of Subject Matter Specialists of Selected Krishi Vigyan Kendras of Northern India - Pankaj Kumar; Prabhjot Kaur (Indian Journal of Extension Education, 2017)
The study was conducted in Punjab, Haryana and Himachal Pradesh selecting 20 KVKs proportionally. A scale was developed to measure the role expectation of SMSs of KVKs comprising 11 role segments viz. organization of trainings, on farm trials, front line demonstrations, programme planning and execution, subject matter authority, communication and feedback, evaluation, management, services and supplies, office work and reporting, and supporting activities. Findings revealed that most of the respondents were male (91.30%), in 46-52 year age category (47.83%), life members of professional societies (100%), having doctorate degree (100%), rural background (82.60%), having nuclear families (52.20%), family occupation service (65.20%) and service experience of 27-35 years (43.48%).Necessary arrangements for the successful conduct of training, selection of location specific problems, proper selection of site for demonstration, implementing or helping in implementation of plan of work, fully conversant with the agricultural situation in the district w.r.t. area of specialization, informing the insect/pest outbreaks/attacks and other calamities which need emergency reporting to concerned authorities, self-evaluation, create team spirit through cooperation and coordination, helping farmers in difficult situation e.g. pest attack, epidemics, drought, flood, preparation and timely submission of various periodic reports prescribed by University and ZPD and publishing the research/extension publications were the top ranked expected roles as expressed by respondents in different role segments respectively. Overall mean expectation score of on-farm trials was highest (4.64) and supporting activities was lowest (4.25). Majority of the respondents (56.52%) were having medium overall role expectation, twenty six per cent low and 17.39 per cent of the respondents were having high overall role expectation.